The Nexus Between Sperm Membrane Integrity, Sperm Motility, and DNA Fragmentation - Alfredo Góngora; Stephen Johnston; Pablo Contreras; Carmen López-Fernández; Jaime Gosálvez (Membranes)
This study investigated the interrelationships between sperm plasma membrane integrity, motility, and DNA fragmentation (SDF) to provide a more holistic understanding of male fertility. A total of 1159 ejaculates were analyzed for sperm membrane integrity (% dead spermatozoa), motility (% immotile spermatozoa), and SDF (% sperm with fragmented DNA). The statistical methods included non-parametric correlation analysis and artificial intelligence (AI)-generated cluster analysis to identify patterns based on these three parameters. The results showed a moderate correlation (ρ = 0.65; p < 0.000) between sperm membrane integrity and motility, indicating that immotile sperm were more likely to exhibit membrane damage. A weak correlation (ρ = 0.21; p < 0.000) suggested that DNA damage was largely independent of the other sperm parameters. Cluster analysis identified three main clusters: Cluster 0: high levels of low membrane integrity, immotile sperm, and moderate DNA fragmentation. Cluster 1: moderate membrane integrity and motility but extremely high DNA fragmentation. Cluster 2: the lowest levels of membrane damage, immotile sperm, and DNA fragmentation, indicating overall better sperm quality. The clustering techniques demonstrated their ability to integrate multiple sperm parameters, enabling a more individualized fertility diagnosis and potentially enhancing male infertility assessments.